Structure of chalcogenide glasses by neutron diffraction - Cuello, Gabriel Julio (2007)
The purpose of this work is to study the change in the structure of the Ge–Se network upon doping with Ag. We report here a neutron diffraction study on two glasses of the system Agx(Ge0.25Se0.75)100−x with different silver contents (x = 15 and 25 at.%) and for two different temperatures (10 and 300 K). The total structure factor S(Q) for the two samples has been measured by neutron diffraction using the two-axis diffractometer dedicated to structural studies of amorphous materials, D4, at the Institut Laue Langevin. We have derived the corresponding radial distribution functions for each sample and each temperature, which gives us an insight about the composition and temperature dependence of the correlation distances and coordination numbers in the short-range. Our results are compatible with the presence of both GeSe4/2 tetrahedra and Se–Se bonds. The Ag atoms are linked to Se in a triangular environment. Numerical simulations allowing the identification of the main peaks in the total pair correlation functions have complemented the neutron diffraction measurements.